2021
DOI: 10.1007/s10964-021-01393-4
|View full text |Cite
|
Sign up to set email alerts
|

It’s All in the Family: Parents’ Economic Worries and Youth’s Perceptions of Financial Stress and Educational Outcomes

Abstract: Perceived economic stress and lower subjective social status (SSS) have adverse effects on parents' and adolescents' emotional well-being, but less is known about associations with academic adjustment among preadolescent youth. This study examined associations between SSS, perceived economic stress about needs and wants, and academic adjustment among preadolescents and early adolescents (n = 136, ages 8 to 14 years, 44% girls, 61% White) and their parents (n = 164, majority middle-to higher SES). Overall, yout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 56 publications
4
23
0
Order By: Relevance
“…For parent-reported financial strain, however, the lack 1 In a multivariate regression analysis, gross monthly family income was a significant predictor of youth-reported financial strain (β = −.17, p = .004) after controlling for parent-reported financial strain (β = .05, p = .404). Mistry and Elenbaas (2021) similarly found that family income was significantly associated with youth perceptions of economic stress after controlling for parent perceptions of economic stress.…”
Section: Moderated Mediation Analysesmentioning
confidence: 88%
See 1 more Smart Citation
“…For parent-reported financial strain, however, the lack 1 In a multivariate regression analysis, gross monthly family income was a significant predictor of youth-reported financial strain (β = −.17, p = .004) after controlling for parent-reported financial strain (β = .05, p = .404). Mistry and Elenbaas (2021) similarly found that family income was significantly associated with youth perceptions of economic stress after controlling for parent perceptions of economic stress.…”
Section: Moderated Mediation Analysesmentioning
confidence: 88%
“…problems, decreasing positive parenting practices, and undermining children's functioning (see Masarik & Conger, 2017). Likewise, youth reporting greater family economic hardship report lower quality interactions with their parents as well as worse psychosocial outcomes (Delgado et al, 2013;Mistry & Elenbaas, 2021).…”
mentioning
confidence: 99%
“…Prior research suggests that higher family SES is positively related to school bonding and engagement (Assari, 2019 ; Li, Doyle Lynch, Kalvin, Liu, & Lerner, 2011 ). Economic and occupational conditions can also create stress at the family level, which can have cascading effects on adolescents’ outcomes (Kim, Kim, Yoo, & Ryu, 2019 ; Mistry & Elenbaas, 2021 ), including school bonding (Assari, 2019 ). Theoretically, socioeconomic stressors can be detrimental to school bonding due to limited financial and social resources and school‐related supports (Budescu & Taylor, 2013 ; Owens & Candipan, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging pandemic‐related scholarship suggests that adolescents showed elevated distress when their parents were essential workers (Mahajan, Kapoor, & Prabhakar, 2020 ; Skokauskas et al., 2020 ). Additionally, extant research on subjective economic hardship illustrates that financial need can be deleterious to adolescents’ school engagement (Mistry & Elenbaas, 2021 ; Yang, Chen, Rhodes, & Orooji, 2018 ). Drawing upon the notion of family stress created by socioeconomic challenges, we examined relations from general (i.e., household income and parental education) and COVID‐19‐specific (i.e., parent essential worker status and pandemic‐related financial need) family socioeconomic factors to longitudinal changes in adolescents’ school bonding.…”
Section: Introductionmentioning
confidence: 99%
“…However, although well-functioning families contribute to positive family outcomes, the absence of an enabling and supportive environment significantly impacts family well-being and functioning [ 13 ]. For example, stressful life events, such as adverse socio-economic challenges and health conditions, can negatively affect the family processes and functioning, leading to family dysfunction which affects the family’s overall well-being [ 14 ]. The Department of Social Development [ 12 ] further argues that COVID-19 played a significant role in consequently impacting the well-being of families in South Africa.…”
Section: Introductionmentioning
confidence: 99%